NILAI PENDIDIKAN KARAKTER PADA KARAKTER TOKOH NADINE ADELLA ULANI DALAM NOVEL ALONE KARYA CHELSEA KARINA - Erlina Zahar; Adzkiya Putri (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2020)
This research is aimed at describing the values of educational character of Nadine Adella Ulani character in the novel Alone by Chelsea Karina. This research is qualitative descriptive. The data were taken from the quotations which are related to the aspects of educational character values of the Nadine Adella Ulani character. In analyzing the data, structural approach technique was used. Based on the analysis of the data, it can be found that there are 10 quotations of educational character values of the Nadine Adella Ulani character in the novel Alone by Chelsea Karina. Those 10 aspects included: 8 quotations of honesty value; 12 quotations of bravery value; 2 quotations of trusteeship value; 3 quotations of wisdom value; 3 quotations of responsibility value; 10 quotations of self-reliance; 3 quotations of shame value; 11 quotations of affection value; 3 quotations of beauty value; and 5 quotations of tolerance value. There are 60 quotations which represent those 10 values. The most dominant value occurred in the novel is bravery value, while the least is trusteeship value.